Eficácia de antissépticos para tetos bovinos elaborado com óleo essencial de alecrim-pimenta no controle de novas infecções intramamárias - Natália Arantes Marcelo (2016)
This study aimed to evaluate a product made with essential oil effect alecrim- pepper (Lippia origanoides) for cleaning ceillings on pathogenic and multiresistant microorganisms to drugs from the mammary gland of cattle. Bacterial genera gropu of Staphylococcus spp. and Streptococcus spp. are microorganisms found in most animals with clinical mastites. The use of antimicrobials in the control of mastitis is of concern in public health for the selection of resistant bacteria, therefore, studies medicinal plants are an alternative to the use of conventional products. Milk samples were used and swabs of teats subjected to pre and post milking sanitization treatment with an experimental product (PEX) the essential oil of rosemary peppermint base and treating with the conventional product (CONV) based on iodine and chlorhexidine. In the milk samples analyzed were identified 10.42% of Streptococcus spp. and 26.56% of coagulase-negative Staphylococcus (SCN), not being identified Staphylococcus aureus. There was no significant difference between the isolated frequency SCN and Streptococcus spp. (p <0.05) in both treatments. The efficacy of the investigational product (PEX) was confirmed with rate of new intramammary infections (NIIM) in the amount of 0.41 to SCN and Streptococcus sp. equal to 0, statistically similar results (p> 0.05) obtained with the conventional product (CONV) and NIIM index which is within the recommended 0.5. It was observed high microbial resistance to oxacillin, penicillin and tetracycline eritormicina, being confirmed with the assessment of multidrug resistance rate to antibiotics (SEA) of 90.9% in S. aureus isolated from ceilings, 35.61% in SCN insulated ceilings, SCN isolated and 93.9% milk, and 15.78% by Streptococcus spp. isolated from milk. There was difference between antimicrobial resistance and PEX and between PEX and oxacillin in the agar diffusion test. The strains of coagulase-negative Staphylococcus isolates from milk and ceilings were different and was not observed identification of Staphylococcus aureus in milk, indicating the product's efficacy in preventing colonization of the interior of the mammary gland by the microflora of the skin of the teats. Isolated skin microbiota teats and milk was multiresistant to conventional antimicrobials and sensitive experimental product made with rosemary peppermint oil indicating that these promising in prophylaxis and treatment of bovine mastitis.